Assessment and determination of earthquake casualty gathering area based on building damage state and spatial characteristics analysis. (January 2022) - Zhang, Leilei; Tao, Zhengru; Wang, Guoxin
Abstract: Timely determination of the spatial distribution of post-earthquake relief forces and appropriate levels of response is a daunting task. This paper proposes a method based on building damage state and spatial characteristics analysis to assess the hotspot distribution of earthquake casualties and determine the dangerous gathering area. The method comprises three steps: (1) use the basic information of the buildings in the study area to calculate the building damage state and build the relationship with the casualties; (2) mesh the research area and establish the mapping relationship with the casualties caused by the building damage; (3) use grid data for spatial autocorrelation analysis (Moran's I) and hotspot analysis (Getis-Ord Gi*) to comprehensively assess the casualty cluster area. The feasibility of the proposed method was validated using the seismic damages of Longtoushan Town in the 2014 Ludian earthquake of China. The damage state of buildings and the number of casualties evaluated by this method coincide quite well with the actual earthquake results, and the casualty concentration area is determined. This method quantifies the degree of spatial risk aggregation of casualties and provides scientific guidance for disaster prevention planning and rescue.